Development and Utilisation of an Instructional Programme for Impacting Competence in Language of Graphics Orientation (LOGO) at Primary School Level in Ibadan, Nigeria (2013)
Computers enhance the process of understanding when used for teaching and learning. This made the Nigerian Government to introduce computer studies into the basic education curriculum. However, the content and activities in the computer basic curriculum are centred mostly around browsing and clicking and not on programming as many believed that programming is for adults. This study, therefore, developed a Language of Graphics Orientation (LOGO) instructional package and investigated its impact on primary school pupils’ competence in LOGO. It also examined the influence of age, gender, computer literacy and school type on competence in the programme. The study adopted one group pretest-posttest quasi-experimental design. A 20-module instructional package was developed based on Kerr’s model of curriculum development. Three hundred and forty-nine pupils aged 5, 6, 7 and 8years and eight computer studies teachers purposively drawn from two private and two public primary schools participated in the study. Five instruments were used: Achievement Test in LOGO (r =0.70), Teachers’ Perception Scale on LOGO, (r = 0.89), Challenges of Package Usage Scale (r =0.72), Utilization Scale for Package (r = 0.75) and Computer Literacy Scale (r = 0.75). Five research questions were answered and five hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, t-test and analysis of variance. The LOGO instructional package was validated in a pilot study; results showed that the package had a good face and content validity which was measured in terms of coverage, sequence and appropriateness for the pupils as perceived by their teachers. Teachers’ perception during the process of development in terms of conceptualisation was 0.8, identification of basic objectives 0.7, designing of package 0.7, try-out 0.7, revision 0.7 and teacher training 0.7. The instructional package was appropriate for pupils’ age 1.0, presentation of illustrations 0.9 and content sequence 1.0. The difference in the pupils’ pretest (x = 4.10) and posttest (x = 27.88) competence mean scores in LOGO was significant (t = 53.56; df = 348; p <0.05). There was significant effect of age on pupils competence in LOGO (F(3,345) = 45.94 p 0.05). Pupils aged 8years had highest mean competence score (x = 34.20) followed by those of age 7 (x =29.71), 6 (x = 26.96) and 5 (x = 20.53). There was no significant effect of gender on pupils’ competence. Furthermore, there was significant effect of computer literacy on pupils’ competence (t=8.26 df= 347 p 0.05) in favour of pupils with high level of computer literacy (x = 31.54). There was significant effect of school type on pupils’ competence (t = 8.13 df = 347 p 0.05) with private school pupils obtaining higher mean score (x = 31.56) than public school pupils (x = 24.38). The developed Language of Graphics Orientation instructional package enhanced the competence of primary school pupils in computer programming irrespective of age, computer literacy level and school type. It is therefore recommended that LOGO should be included in computer studies curriculum for primary schools as from age six.